Expatriation, Repatriation, and Domestic Geographical Relocation: An Empirical Investigation of Adjustment to new Job Assignments - Feldman, Daniel C.; Tompson, Holly B. (Journal of International Business Studies, 1993)
This research examines the relative impact of six sets of factors on multiple indices of adjustment to new job assignments. These six sets of factors include demographic variables, indices of the “internationalness” of the job change (e.g., whether the job changer is an expatriate, repatriate, or domestic geographical relocator), job characteristics variables, types and amount of career development assistance, degree of change between successive job assignments, and types of individual coping strategies employed by job changers. Data were collected from 459 job changers from twenty-six countries. The results highlight both the commonalities among expatriates, repatriates, and domestic geographical relocators in adjusting to new job assignments as well as the differences among them.